Analysis topography of robot laser hardened materials by using machine learning method - Babič, Matej (Anali PAZU, 2022)
Laser treatment of materials, including heat treatment, is based on the use of laser radiation, which allows you to create, on a very small surface, the high thermal field densities required for intense heating or melting. The article presents the influence of the robot laser cell parameter on the material topography. Machine learning methods show how the parameters of a robot laser cell affect the hardness and roughness of the hardened material, and the relationship between hardness and roughness.
Keywords: laser; robot; machine learning